Leveling the playing field of transportation fuels: Accounting for indirect emissions of natural gas. (August 2016) - Sexton, Steven; Eyer, Jonathan
Abstract: Natural gas transportation fuels are credited in prior studies with greenhouse gas emissions savings relative to petroleum-based fuels and relative to the total emissions of biofuels. These analyses, however, overlook a source of potentially large indirect emissions from natural gas transportation fuels, namely the emissions from incremental coal-fired generation caused by price-induced substitutions away from natural-gas-fired electricity generation. Because coal-fired generation emits substantially more greenhouse gases and criteria air pollutants than natural-gas-fired generation, this indirect coal-use change effect diminishes potential emissions savings from natural gas transportation fuels. Estimates from a parameterized multi-market model suggest the indirect coal-use change effect rivals in magnitude the indirect land-use change effect of biofuels and renders natural gas fuels as carbon intensive as petroleum fuels. Highlights: Natural gas used in transport causes indirect emissions in the electricity sector. These emissions result from increased coal use in electricity generation. They rival in magnitude indirect land use change (ILUC) emissions of biofuels. Natural gas fuels are estimated to be as carbon intensive as the petroleum fuels. Policy ignores indirect emissions from natural gas.